1994
DOI: 10.1007/bf02260363
|View full text |Cite
|
Sign up to set email alerts
|

Providing antenatal services in a primary health care system

Abstract: A study sample of 880 women attending the primary health care center in the Al-Baha region of Saudi Arabia was interviewed on their attitudes towards antenatal care services in the primary care setting. Some 91.3% of the women expressed positive views about obtaining the antenatal care in these centers. The major factor influencing their choice was the geographic location of primary health centers which are near to their residence and therefore more convenient for them to patronize. Other factors were the easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…In spite of the closeness to a health facility, only 27.9% of live births were delivered at such health facilities 2 , suggesting that 22.1% of the expectant women did not deliver at a health facility despite being within reach of a health facility. There is overwhelming evidence that distance to a health facility is a strong determinant of the choice for maternal health services 3,4 , However, factors other than distance to health facility have been reported to be associated with health service utilization for childbirth such as education [5][6][7][8] , maternal age 3,6 , parity 6,8 , economic status 7 , cultural factors and beliefs, lack of skilled staff at primary health care level, and health worker negative attitudes towards expectant mothers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the closeness to a health facility, only 27.9% of live births were delivered at such health facilities 2 , suggesting that 22.1% of the expectant women did not deliver at a health facility despite being within reach of a health facility. There is overwhelming evidence that distance to a health facility is a strong determinant of the choice for maternal health services 3,4 , However, factors other than distance to health facility have been reported to be associated with health service utilization for childbirth such as education [5][6][7][8] , maternal age 3,6 , parity 6,8 , economic status 7 , cultural factors and beliefs, lack of skilled staff at primary health care level, and health worker negative attitudes towards expectant mothers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Studies conducted on the relationship between travel distance and the rate of utilization of maternal and child healthcare services showed that with increasing distance there was an associated lower utilization of health services. 14,[23][24][25][26][27] Participants in this study who traveled more than five kilometres to reach the health facility utilised the maternal and child health services less than those who traveled less than five kilometres. Distance has also been found to affect clinic attendance especially in rural areas where transportation may be a problem for some people who come from distant villages.…”
Section: Discussionmentioning
confidence: 99%
“…X2=43.56 p<0.01) Bu sonuçlar, üzerinde çalışılan grup için, birinci basamak hizmetlerinin çok yaygın, ulaşılabilir yada talep edilebilir olmadığını göstermektedir. Buna karşın pekçok ülke örneği,hem yakın hem de ekonomik olmaları nedeniyle DÖB'da birinci basamak merkezlerin tercih edildiğini göstermektedir (6,7).…”
Section: Discussionunclassified
“…Ayrıca bir meslek hastalığı şeklinde, veterinerler, çiftçiler, kasaplar ve mezbaha işçilerinde infeksiyona sık rastlanmaktadır (4,5). Bruselloz %85 oranında erkeklerde, daha çok bahar ve yaz aylarında görülmek-tedir (6,7). Bruselloz, gelişmiş ülkelerden birçoğunda eradike edilmiş ya da kontrol altına alınmış olmasına rağmen, Türkiye gibi gelişmekte olan ülkelerde, endemik olarak görülmeye devam etmekte ve epidemiyolojik ça-lışmalara rağmen genellikle gerçek prevalans bilnememektedir.…”
unclassified